Antecedents of Continuous Usage Intention of Mobile Banking Services from the Perspective of DeLone and McLean Model of IS Success - Al-Ghazali, Basheer Mohammed; Rasli, Amran Md; Yusoff, Rosman Md; Mutahar, Amena Yahya (International Journal of Economics and Financial Issues, 2015)
Mobile banking has been attested to play an important role in customer satisfaction therefore retention and inclination of the customers to decide and sustainable usage of the banking services. Presumably, relative advantage, post-use-trust influence and attitudinal loyalty plays important role in the decision of the continuous usage of mobile banking. In addition to the specific factors, there are other important factors, which are required to be identified and modelled in evaluating the tendencies and intentions of continuous usage of mobile banking. To discuss these and similar other factors affecting the customers post-use-trust, this study extends the key framework of DeLone and McLean (2003) by assessing the efficacy of the determinants of the post-adoption satisfaction and intention of continuous usage. Expected modification includes the identification of the effects of the relative advantage, post-use-trust influence and attitudinal loyalty. A key expectation of this study is to review the aspects of retention models in literature and hence propose a generalized approach towards identification and assessing determinants of overall satisfaction of mobile banking customers generally and specifically of the intention of post-adoption and continuous usage and post-use-trust. It is expected that evidence of such modification and extension of the framework will lead to conclusion and findings towards key factors of post-adoption satisfaction and customer inclination and intention towards continuous usage of mobile banking and hence will be beneficial for the banking sector researchers. Keywords: mobile banking; customer satisfaction; customer retention; post-use trust; DeLone and McLean Model JEL Classification: M000